DILEMA DIGITALISASI PENYIARAN TANTANGAN REGULASI BROADCASTING DI ERA KONVERGENSI MEDIA DI INDONESIA - Lubis, Muhammad Rahmadani; Sazali, Hasan (FIKRUNA: Jurnal Ilmiah Kependidikan dan Kemasyarakatan, 2025)
Digital transformation in broadcasting has had a significant impact on the media sector and broadcasting regulations in Indonesia. In the context of accelerating media convergence, the broadcasting industry is faced with the challenge of adapting to technological advancements, new policies, and global dynamics. This research aims to explore the challenges faced in broadcasting regulation in Indonesia, especially in the era of media convergence, with an emphasis on digitalization that changes the way information is conveyed to the public. The methodology used in this study is a qualitative approach, which includes literature studies and in-depth interviews with policymakers and media practitioners in the country. The findings of this study show that although digitalization provides significant opportunities for the growth of the broadcasting industry, various regulatory challenges need to be overcome, such as content control, frequency distribution, and protection of freedom of expression and information access rights for the public. In addition, this study reveals that media convergence requires more adaptive and inclusive regulatory adjustments, involving various stakeholders in formulating policies that support innovation, without ignoring the social and cultural values that exist in Indonesia.